Heterostigmatic mites (Acari: Trombidiformes: Prostigmata) associated with Coleoptera and Hymenoptera in Mazandaran province, northern Iran - Hamidreza Hajiqanbar; Elham Arjomandi (Persian Journal of Acarology)
In a study on insect-associated heterostigmatic mites (Acari: Trombidiformes: Prostigmata) carried out in Mazandaran province, northern Iran, during spring and summer 2016–2017, a total of 13 species from 11 genera of six families were identified. Among them, three species Imparipes sevastianovi Khaustov, 2008, Scutacarus hystrichocentrus Sevastianov, 1983 (Scutacaridae), and Petalomium kurosai Khaustov, 2014 (Neopygmephoridae) are new records for mite fauna of Iran. The S. hystrichocentrus is also new for Asian mite fauna. Eight new host records are documented and the distributions of the mites are revised. Beetles of the family Cerambycidae are recorded as host of the mite families Microdispidae and Scutacaridae for the first time.